Analisis Faktor yang Berhubungan dengan Budaya Keselamatan Pasien pada Perawat di Ruang Rawat Inap RSUD Arifin Achmad Provinsi Riau - Yeni Yarnita; Efitra Efitra (Universitas Batanghari Jambi, 2020)
Safety patient culture was one of the important things in operating the safety patient in hospital, so that the unexpected incident can be minimized. the data Arifin Achmad Riau Province showed that the number exceeds the limit figure KTD specified tolerance ie ≥ 1.5% like numbers plebitif 5.81%, and the incidence of patient falls are as much as five events in 2015. This research is aimed to know the factors which are related to the safety patient culture on nursing staff in hospitalization service room of Arifin Achmad Hospital, Riau Province. The population is all of the nursing staffs in Arifin Achmad Hospital, Riau Province with the sample is 131 nurses. This research uses cross sectional non probability sampling technique. The method in collecting the data is questionnaire and the method in analyzing the data are frequency distribution, chi square distribution and logistic regression test. The result of the research is obtained there is a relation between attitude (p value 0.001), team work (p value 0,017), fatigue (0,013) with the safety culture, while the stress work does not related to the safety patient culture (p value 0,139). The result obtained that attitude is the most related factor with the safety patient culture. The writer suggests to the management of the hospital to be able to enhance the safety culture management support, improve peedback safety culture and communication between leaders and nurses, workforce analysis, structuring nurse station